A self-adaptive IoT architecture to support intelligent environments - Nascimento, Mateus G. do; David, José Maria N.; Dantas, Mario A. R.; Braga, Regina; Ströele, Victor (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
Context: Intelligent environments are complex interaction spaces between people, sensors, devices, and systems. The Internet of Things (IoT) has provided, in recent years, the gradual exposure of society to these environments. However, Software Engineering requires specific techniques to deal with the development of these systems. Software Engineering must tackle the intrinsic characteristics of devices and sensors and complex interactions in intelligent environments to consolidate good development practices. Objective: The main objective of this article is to present a self-adaptive IoT architecture in an intelligent environment. The proposal concerns how different architecture modules cooperate and interact to develop new applications. Method: The work was developed through a real-world case study in an intelligent e-health environment. Conclusion: The results showed how a self-adaptive architecture using artificial intelligence can support the management of an intelligent e-health physical space. With this, it was possible to observe how data collection, environment monitoring, prediction of using IoT devices, and optimization of environment management can occur.